marketing mix, covid-19, micro b MARKETING MIX OF MICRO ENTERPRISES DURING THE COVID-19 PANDEMIC IN KEBONJATI VILLAGE, NORTH SUMEDANG SUB-DISTRICT, SUMEDANG REGENCY - Diana, Diana (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2023)
The COVID-19 pandemic is a major problem currently being faced by more than 200 countries including Indonesia. The COVID-19 pandemic not only shows negative impacts but on the other hand there are opportunities that also arise such as the interaction between humans and technology. Micro, Small and Medium Enterprises (MSMEs) are one of the economic sectors affected by the COVID-19 Pandemic. The purpose of this study is to identify the marketing mix (product, price, place, and promotion) applied by micro businesses in Kebonjati Village, North Sumedang District, Sumedang Regency during the COVID-19 period. The method used in this research is descriptive qualitative, using data obtained or collected directly from in-depth interviews and documentation studies. The results showed that the strategy of determining M business products during the pandemic was carried out by maintaining production and maintaining product taste and quality. The strategy of determining outlets and distribution is severely hampered during the pandemic so that M businesses strive for existing outlets to continue operating. The strategy of determining the price of M business products during the pandemic was carried out through deliberations with the G Tofu Craftsmen Association to consider the cost of production, quality of goods, consumer ability, and competitor prices. The promotion strategy carried out by M businesses is direct promotion to consumers of outlet traders through personal selling and sales promotion. During the pandemic, promotions were carried out through digital media such as WhatsApp, Instagram, and Facebook. Keywords: covid-19, marketing mix, micro business.